STRUCTURE AND SEMANTIC PROPERTIES OF VERBS IN THE ENGLISH AND UZBEK LANGUAGES - Qurbonboyeva Hilola, (TADQIQOTLAR, 2025)
A comprehensive examination of the structural and semantic characteristics of verbs in English and Uzbek reveals both striking similarities and notable differences shaped  by  their  respective  linguistic  typologies.  English,  belonging  to  the  Indo-European  family,  and  Uzbek,  a  representative  of  the  Turkic  language  group,  offer unique  perspectives  on  verb  formation,  grammatical  categorization,  and  semantic representation.  This  study  investigates  the  morphological  patterns,  including  verb inflection  and  derivation  processes,  as  well  as  the  systems  of  tense,  aspect,  and modality  (TAM)  in  both  languages.  Additionally,  the  research  analyzes  how  verbs assign semantic roles such as agent, experiencer, theme, and beneficiary in sentence structures.  Through  comparative  linguistic  analysis,  key  areas  of  convergence  and divergence are identified, especially in relation to verb valency, argument structure, and the expression of modality. The results underscore the complexity and richness of verbal systems in both languages, highlighting the influence of agglutinative versus analytic structures on meaning construction. Insights gained from this study contribute to  the  broader  understanding  of  cross-linguistic  verb  semantics  and  have  practical applications  in  areas  such  as  bilingual  education,  language  acquisition,  and  the development of accurate translation models between English and Uzbek.